2021
DOI: 10.1016/j.jshs.2020.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing athletes’ sleep: A systematic review of the influence of age, sex, athletic expertise, sport type, and season on sleep characteristics

Abstract: Highlights Several exercise- and sports-related parameters such as sex, age, athletic expertise, training season, and sports type are discussed. These factors may potentially influence sleep quantity and architecture. Overall, sleep quantity and quality in athletes is reduced and potentially insufficient, in comparison to the general consensus of the American Academy of Sleep Medicine for non-athlete healthy adults. Specifically, young athletes, mainly of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 113 publications
(133 reference statements)
3
29
0
Order By: Relevance
“…Interestingly the PSQI mean TST (<8 h) was lower than that reported in the CSD-C (>8 h), it has been suggested that athletes tend to overestimate their sleep [ 104 , 105 ]. A recent review suggested that sleep in athletes is limited to 7.2 h per night, with all studies reporting <8 h per night and mean SE was 86.3 ± 6.8% [ 106 ], which is in line with the PSQI and CSD-C data from the current study. The PSQI mean TST for both groups in the current study is adequate according to current sleep recommendations (7–9 h) [ 48 ].…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly the PSQI mean TST (<8 h) was lower than that reported in the CSD-C (>8 h), it has been suggested that athletes tend to overestimate their sleep [ 104 , 105 ]. A recent review suggested that sleep in athletes is limited to 7.2 h per night, with all studies reporting <8 h per night and mean SE was 86.3 ± 6.8% [ 106 ], which is in line with the PSQI and CSD-C data from the current study. The PSQI mean TST for both groups in the current study is adequate according to current sleep recommendations (7–9 h) [ 48 ].…”
Section: Discussionsupporting
confidence: 88%
“…As training load could further affect sleep, this must be stressed as a limitation to the study. 15 However, elite athletes often face training camp or competition phases in which they do not sleep at home, have inconsistent food intake, and do not have perfectly controllable training and sleeping environment. Consequently, it is of great interest to examine whether portable PSG is reasonable in these particularly high demanding situations as diagnostics will often be applied in these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…2 Yet, in-laboratory PSG is not feasible in sport-scientific field studies; hence, most of the sleep data in a population of athletes is obtained by using subjective questionnaires or wrist actigraphy as they are portable, non-invasive, and no specialist is needed to secure the recording. 11,[14][15][16] However, as no EEG measures are recorded, it is not possible to score sleep stages with these methods. Thus, they cannot measure physiological aspects of sleep.…”
Section: Introductionmentioning
confidence: 99%
“…The required sleep quantity varies among individuals and its adequacy is reflected by the absence of sleep-induced or sleep-related health issues, daytime dysfunction or sleepiness [4]. Insufficient sleep traits have been increased over the last years [5,6]. Its association with numerous diseases [7] underlined the necessity to examine practical and effective approaches, including manipulation of nutritional aspects to optimize sleep [8].…”
Section: Introductionmentioning
confidence: 99%